Case report: Glucose 6-phosphate-isomerase deficiency combine with avascular necrosis of bilateral femoral head - Song, Zhenqi; Wang, Kongjian; Arthur, Djandan Tadum; Tang, Zhongwen; Xiang, Feng; Wen, Jie; Xiao, Sheng (Frontiers in Pediatrics, 2022)
Background Glucose 6-phosphate-isomerase deficiency (GPI) is an uncommon autosomal recessive genetic disorder characterized by chronic asphoric hemolytic anemia, jaundice, and hepatospleenomegaly of varying degrees. Avascular necrosis of the femoral head in children may be caused by Legg-calve-perthes disease or hematological diseases. However, to date, there is no literature reporting on femoral head avascular necrosis as a complication of GPI. Case presentation Herein we report a 6-year-old child admitted with no pain and abnormal gait in both lower extremities for 3 years, the patient received a genetic inspection and radiology test. Full-exon detection and Sanger sequencing verification were performed on the children and their parents C. 553T>A homozygous missense mutation (NM_ 001289790, F 185 I) was found in exon 6 of the GPI gene, which was inherited from parents. The radiology test showed avascular necrosis of the bilateral femoral head. The patient received traction and wore a spica splint every night and non-weight bearing hip joint rehabilitation every day for 12 months, after which, the gait of the femoral head of this patient improved significantly, and follow up radiation results showed the area of avascular necrosis of the femoral head had decreased. Conclusion Careful investigation of GPI children with abnormal gait is recommended to avoid misdiagnosis, GPI combined with avascular necrosis of the femoral head should be considered as a differential diagnosis in GPI children with abnormal gait.